"A vida", "O balão" e "O pássaro": análise de uma política de formação de leitores na perspectiva inclusiva - Real, Daniela Corte (My University, 2020)
This Thesis aims is to analyze the materiality of collections and the use of PNBE, based on Bakhtin’s Dialogic Discourse Analysis (ADD), with the purpose of proposing accessibility indicators that could help the development and implementation of reading policies in the inclusive perspective. This academic writing is organized into three parts, the balloon trip metaphor is used. It was necessary to define how to travel. In this sense, I can say that the balloon trip is qualitative because it admits the interference of the traveler / researcher and considers the existence of multiple realities according to (JUNG, 2004). In Part I – “The Life” I introduce myself and some questions about the use of children's literature in classroom and I bring important concepts by Bakhtin (2010, 2007, 2004) that anchor the theoretical discussion about linguistic community, language, speaker, receiver, dialogue, dialogism, polyphony, utterance, enunciation, discursive will, responsive attitude, interaction and culture. On “The Balloon” (Part II), I define concepts such as: accessibility, inclusive perspective, Public Policies and Public Policies for the formation of readers; I search to contextualize the Programa Nacional Biblioteca da Escola/ PNBE; I introduce the locus of the research (four schools located in Caxias do Sul belonging to the 4º Coordenadoria Regional de Educação – 4º CRE, one special school and three regular schools; the passengers (teachers who work with the formation of literary readers, which are filled in the school libraries and teachers of Atendimento Educacional Especializado/AEE. Accounted 10 teachers), and the script of questions – methodological design, I describe and analyze the situations of enunciation and systematize the new flight maps found from the ADD without losing the idea about the formation of literary readers in the inclusive perspective that guided my readings. When I bring, “The bird” (Part III) I risk, final considerations such as the need to establish directives within which there is a shared responsibility system and co-partnerships between different social actors for the implementation of public policies public that work and their function concerning readers development in this country with greater efficiency; the development of actions aiming the qualification of teachers and library professionals, among others, for the mediation of children's literature in a dialogical and inclusive perspective; and conducting research to map and diagnose public policies for readers' development in Brazil to na inclusive perspective. And I bring some questions that may direct the continuity and / or developments of this trip / research. Questions that restless, that motivate and cause strangeness as: the death of the reader; the understanding of accessible but not available; and the INvisibility of PNBE.
Esta Tese tem como objetivo analisar a materialidade dos acervos e o uso do PNBE, a partir da Análise Dialógica do Discurso (ADD), de Bakhtin, com a finalidade de propor indicadores de acessibilidade, que pudessem auxiliar o desenvolvimento e a implementação de políticas de leitura, na perspectiva inclusiva. Organizada em três partes, a partir da utilização da metáfora da viagem de balão, foi preciso definir como viajar e, nesse sentido, posso dizer que a viagem de balão é do tipo qualitativa, porque admite a interferência da viajante/pesquisadora e considera a existência de múltiplas realidades. (JUNG, 2004). Na Parte I – “A Vida” me apresento, introduzo algumas questões em relação ao uso da literatura infantojuvenil em sala de aula e trago conceitos importantes de Bakhtin (2010, 2007, 2004), que ancoram a discussão teórica como: comunidade linguística, linguagem, locutor, receptor, diálogo, dialogismo, polifonia, enunciado, enunciação, vontade discursiva, atitude responsiva, interação e cultura. Em “O Balão” (Parte II), defino conceitos como: acessibilidade, perspectiva inclusiva, políticas públicas e políticas públicas para a formação de leitores; busco contextualizar o Programa Nacional Biblioteca da Escola/PNBE; apresento o locus da pesquisa (quatro escolas localizadas em Caxias do Sul pertencentes à 4ª Coordenadoria Regional de Educação – 4ª CRE, sendo uma escola especial e três regulares; as passageiras (professoras que trabalham com a formação de leitores literários, que estão lotadas nas bibliotecas escolares e professoras do Atendimento Educacional Especializado/AEE, 10 ao todo); e o roteiro de perguntas – delineamento metodológico; descrevo e analiso as situações de enunciação e sistematizo os novos mapas de voo encontrados a partir da ADD, sem perder de vista que a formação de leitores literários, na perspectiva inclusiva, orientou minhas leituras. Ao trazer “O Pássaro” (Parte III), arrisco considerações finais como: a necessidade de estabelecimento de diretrizes de corresponsabilidade e coparcerias entre os diferentes atores sociais, para a implementação das políticas públicas à formação de leitores no País com maior eficiência; o desenvolvimento de ações com vistas à qualificação dos professores e profissionais das bibliotecas, entre outros, para a mediação da literatura infantojuvenil, numa perspectiva dialógica e inclusiva; e a realização de pesquisas para o mapeamento e diagnóstico das políticas públicas para a formação de leitores no Brasil na perspectiva inclusiva. E trago algumas questões que podem encaminhar a continuidade e/ou os desdobramentos desta viagem/pesquisa. Questões que desassossegam, que motivam e causam estranhamento, como: a morte do leitor; o entendimento de acessível, mas não disponível; e a INvisibilidade do PNBE.
Keywords: Leitura; Política pública; Bibliotecas escolares; Bibliotecas e usuários; Educação inclusiva; Reading; Public policy; School libraries; Public services Libraries; Inclusive education